MP16: SCREENING FOR INFECTIVE ENDOCARDITIS AMONG PATIENTS IN AN INNER CITY HOSPITAL. Issue 3 (23rd February 2016) - Sharma, R; Garg, E; Conaway, D; Garg, M
Abstract : Purpose of Study: Over the years, epidemiology of infective endocarditis (IE) has been changing with the change in population at risk. The aging of our population, better antibiotics for treatment of infections and changes in predisposing conditions have contributed to the changing prevalence patterns of this disease in different patient groups. At present little data is available on the prevalence of IE in selected patient groups such as the medically indigent. We studied the prevalence of IE in patients evaluated in an inner city hospital. Methods Used: We screened the clinical, laboratory and echocardiographic data of 246 consecutive patients referred for echocardiographic evaluation, with suspected IE during the period 04/1996 to 05/ 2001. Using the New Duke criteria for diagnosing endocarditis, these patients were classified as having 1. Definite IE 2. Possible IE and 3. Diagnosis of IE rejected. Summary of Results: Of the 246 patients screened, 72 (29%) fulfilled criteria for diagnosis of IE. Twenty of these patients (8%) were classified as "definite" IE and 52 (21%) as "possible" IE. Diagnosis of IE was "rejected" in 174 (71%) of the screened patients. Conclusions: Screening for IE in this medically indigent patient population of an inner city hospital, confirmed definite endocarditis in only 8% of the patients referred with suspected endocarditis. This represents a very small proportion of the patients screened and is much lower than reported in other studies, in a different patient population. This could be due to a higher degree of suspicion for IE in this patient group. Further inquiry is needed to confirm the underlying mechanism responsible for this observation.